Management of Lithium Batteries in the Treatment of Weee: Dispersion Modelling and Containment Measures Applied to an Italian Case Study - Chiara Vianello; Giosuè Pasqualotto; Lorenzo Baraldo; Giulia De Cet; Giuseppe Maschio (Chemical Engineering Transactions, 2025)
Fires originating from Waste from Electrical and Electronic Equipment (WEEE) containing lithium batteries pose a significant challenge for waste management facilities. This article aims to define fire containment measures for treatment plants and evaluate their effectiveness through a case study. After an overview of WEEE regulations and the risks associated with lithium batteries, both as standalone units and within electronic devices, the study analyzes a case study involving a WEEE treatment facility. It evaluates the consequences of an uncontrolled fire, specifically emissions from plastic items in WEEE storage. Using the ALOFT program, fire scenarios were modeled to assess the dispersion of volatile organic compounds (VOC) and Particulate matter (PM10). The study underscores the importance of addressing lithium battery fires in WEEE to support the EU’s recycling goals and ensure environmental and worker safety through a multi-partner approach.